Granulocyte colony-stimulating factor and drugs elevating extracellular adenosine act additively to enhance the hemopoietic spleen colony formation in irradiated mice - Hofer, M; Pospísil, M; Netíková, J; Znojil, V; Vácha, J (Physiological research, 1999)
The effects of combined administration of two drugs elevating extracellular adenosine, namely dipyridamole (DP) and adenosine monophosphate (AMP), and granulocyte colony-stimulating factor (G-CSF) on hemopoietic stem cells in vivo were investigated. The experiments were performed on mice using the endogenous spleen colony formation in gamma-irradiated animals as an endpoint. The results have shown that DP and AMP act additively with G-CSF to enhance spleen colony formation and thus the erythroid repopulation of the spleen. These findings indicate that the signaling pathways of G-CSF and drugs elevating extracellular adenosine can interact at the level of primitive hemopoietic stem cells. The enhancement of hemopoiesis-stimulating effects of G-CSF by DP and AMP, which are low-priced and clinically available drugs, could improve the cost-effectiveness of the therapy with G-CSF.
Keywords: Adenosine; Erythroid Precursor Cells; Gamma Rays; Dipyridamole; Hematopoiesis; analýza kolonii tvořících jednotek; počet buněk; záření gama; hematopoetické kmenové buňky; zvířata; myši; Whole-Body Irradiation; faktor stimulující kolonie granulocytů; erytroidní prekurzorové buňky; Mice; hematopoéza; adenosin; Colony-Forming Units Assay; Cobalt Radioisotopes; Adenosine Monophosphate; Male; dipyridamol; celotělové ozáření; Spleen; Extracellular Space; Granulocyte Colony-Stimulating Factor; Hematopoietic Stem Cells; Animals; radioizotopy kobaltu; mužské pohlaví; adenosinmonofosfát; Cell Count; slezina; extracelulární prostor